(untitled) (Sociologisk Forskning, 2024)
This cross-sectional study investigates the shifts in anxiety levels among Swedish employees throughout the Covid-19 pandemic, with data gathered in 2016, 2018, and 2020. Work-related anxiety was assessed through two metrics: General Work Anxiety (WA) and Work Performance Anxiety (WPA). Overall, there was a decline in both average WA and WPA over the five-year period. However, this trend did not apply uniformly across all social groups. Specifically, WA saw a significant decrease among older men, while it showed an increase among younger women. Additionally, the reduction in WPA was more pronounced among managers than employees during the pandemic. High-income individuals and those with advanced education levels also experienced a greater decrease in WPA. These findings underscore the role of employment conditions in shaping the impact that the pandemic might have had on workers’ mental health.